Fire Impact Assessment of Flammable Fuel Storage in Heat Treatment Plant Using Fire Dynamic Simulator - V.Kurinji,; R.Rajkumar,; S.Prabhakaran,; K.Umanath,; D.S.Balaji, (International Journal of Psychosocial Rehabilitation, 2020)
Today we use highly durable materials in our day to day life. Some material used for manufacturing of mechanical components and infrastructure projects requires high strength and durability. To make a component highly durable heat treatment is done to fulfill the requirement of particular needs of a component. The Heat Treatment process increases the strength of the material by modifying their metallurgical properties. In Heat Treatment facility, the fire hazards are comparatively high and even a single fire accident may be catastrophic due to the congested and complex layout of the facility. This study proposes a novel methodology for modelling the impact of a fire event in a Heat Treatment facility. Hazard identification and accident credibility assessment have been used to discover the most credible fire accident scenarios. These scenarios have been simulated using Computational Fluid Dynamics (CFD) code, Fire Dynamics Simulator (FDS). The results have then been compared to identify the most severe impact of the fire on personnel and assets using thermal radiation and risk levels. It has been found that the fire event in scenarios has a high potential to cause damage to adjacent assets. From this comparison, it is evident that the scenario in the fuel storage and transmission pipe lines in the combustion process has the highest risk of fire to both personnel and assets. The proposed methodology may be adapted further for safety measure design to mitigate or avoid the impacts of a fire event in any complex processing facility.